2023
DOI: 10.1186/s13046-023-02683-4
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine applied to metastatic colorectal cancer using tumor-derived organoids and in-vitro sensitivity testing: a phase 2, single-center, open-label, and non-comparative study

Abstract: Background Patients with colorectal metastatic disease have a poor prognosis, limited therapeutic options, and frequent development of resistance. Strategies based on tumor-derived organoids are a powerful tool to assess drug sensitivity at an individual level and to suggest new treatment options or re-challenge. Here, we evaluated the method’s feasibility and clinical outcome as applied to patients with no satisfactory treatment options. Methods I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Previous studies sampling CRC biopsies from metastatic sites have reported culture success rates of 54%–63% using culture methods with PDTO embedment into solid support matrices. 13 , 37 , 38 In the AGITG FORECAST-1 study, we achieved a similar 63% overall success rate for PDTO LVM cultures 25 and identified CRC liver metastases as the optimal biopsy site for PDTO generation with a 75% success rate (compared to 50% for other sites). Nonetheless, PDTO culture success rate remains a major barrier to eventual clinical translation with biopsy size, tumor cell content, and viability established as critical factors for success 18 , 38 ; further improvements in PDTO success rate may be achieved by increasing biopsy number and/or size and by further optimization of culture conditions such as replacement of classic niche factors with emerging biomimetic compounds or introduction of new biopsy methods.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies sampling CRC biopsies from metastatic sites have reported culture success rates of 54%–63% using culture methods with PDTO embedment into solid support matrices. 13 , 37 , 38 In the AGITG FORECAST-1 study, we achieved a similar 63% overall success rate for PDTO LVM cultures 25 and identified CRC liver metastases as the optimal biopsy site for PDTO generation with a 75% success rate (compared to 50% for other sites). Nonetheless, PDTO culture success rate remains a major barrier to eventual clinical translation with biopsy size, tumor cell content, and viability established as critical factors for success 18 , 38 ; further improvements in PDTO success rate may be achieved by increasing biopsy number and/or size and by further optimization of culture conditions such as replacement of classic niche factors with emerging biomimetic compounds or introduction of new biopsy methods.…”
Section: Discussionmentioning
confidence: 68%
“…The duration of PDTO expansion prior to in vitro treatments depends on tumor cell proliferation rate and the required cell input and number of assay points. 13 , 37 , 38 For AGITG FORECAST-1, we required 4–21 weeks to examine 9 single agents in duplicate 9-step dose titrations and 2 drug combinations in duplicate 7 × 7 matrices. However, PDTO assay miniaturization to a 2-point window was found to maintain and potentially improve prediction accuracy and association with PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propidium iodide and Hoechst have previously demonstrated their suitability for high-throughput screening of colorectal adenoma PDOs [ 39 ]. CyQUANT was used previously in a prospective organoid-guided interventional trial with positive results, albeit with modest clinical benefit [ 40 ]. We confirmed that drug sensitivity measurements with the CyQUANT readout instead of the ATP-based CellTiter-Glo readout was possible in 3D-based screens and did not affect the correlation with patient response.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 2 study involving 90 mCRC patients with progression after standard therapy, organoids derived from metastatic biopsies were cultured and evaluated for sensitivity to a panel of drugs. Patients were treated with the drug demonstrating the highest relative activity, resulting in a 50% progression-free rate at two months [ 83 ] . Another study generated organoids from 40 mCRC patients and performed drug screenings, associating the results with patients’ responses.…”
Section: Applications Of 3d Culture Systems In Drug Resistance Researchmentioning
confidence: 99%